Manajemen Strategis dalam Implementasi Misi Mencintai Selamanya di Institut Pendidikan Kejuruan Awal Changchun Tiongkok - Jiajun, Zhai; Dewi Listyasari , Winda; Ika Mayasari, Linda (Jurnal Ragam Pengabdian, 2026)
This study investigates the strategic management practices implemented in the “Loving Forever” mission at Changchun Early Education Vocational Institute, China. The research focuses on three major aspects: strategic planning, strategy implementation, and strategy evaluation in supporting mission-oriented vocational early childhood education. This study employed a qualitative approach with a grounded theory design. Data were collected through in-depth interviews, observations, and document analysis involving institutional leaders, lecturers, administrative staff, and students. The findings reveal that the institution has systematically integrated the “Loving Forever” mission into its strategic planning, organizational culture, curriculum, and educational programs. Strategy implementation was carried out through human resource management, organizational structure strengthening, and practice-based learning programs. Furthermore, strategy evaluation was conducted through monitoring, supervision, and corrective actions to maintain alignment with institutional goals. However, challenges remain in stakeholder participation, communication, and operational understanding of the institutional mission across organizational levels.